Electrochemical behavior of cobalt oxide coatings on cold-rolled steel in alkaline sodium sulfate - Silva, G. C.; Fugivara, Cecilio Sadao [UNESP]; Tremiliosi, G.; Sumodjo, PTA; Benedetti, Assis Vicente [UNESP] (Elsevier B.V., 2002)
The electrochemical behavior of a coating of cobalt oxide on cold-rolled steel in alkaline sodium sulfate was Studied using the electrochemical techniques of open-circuit potential measurements and electrochemical impedance spectroscopy. The coating was prepared at different annealing temperatures ranging from 350 to 750 degreesC and characterized by SEM, EDX and XRD. Below 550 degreesC the composition of the coating was basically of Co3O4. At 750 degreesC CoO was formed and big cracks appeared on the film exposing an inner layer of iron oxides. Analysis of the EIS data is very difficult because of the complexity of the interface structure. It can be inferred that the charge transfer resistance of the coatings prepared at 350 and 450 C were higher than those for the coatings prepared at temperatures above 550 degreesC. (C) 2002 Published by Elsevier B.V. Ltd.
Keywords: cobalt oxide coatings; cold-rolled steel protection; coatings characterization; thermal stability of oxides; corrosion